The Effect of Phase Separation on the Mechanical Behavior of the Co–Cr–Cu–Fe–Ni High-Entropy Alloy - Heling Liu (MDPI AG, 2021)
Phase separation phenomena in high-entropy alloys (HEAs) have attracted much attention since their discovery, but little attention has been given to the dynamics of the deformation mechanism of this kind of HEA during uniaxial tension, which limits their widespread and practical utility. In this work, molecular dynamics simulation was used to study the effect of phase separation on the mechanical properties of an HEA under uniaxial tensile loading. Moreover, the associated deformation behavior of the Co–Cr–Cu–Fe–Ni HEA was investigated at the nanoscale. Models with Cu-rich grain boundaries or grains were constructed. The results showed that Cu-rich grain boundaries or grains lowered the strength of the Co–Cr–Cu–Fe–Ni HEA, and Cu-rich grain boundaries significantly reduced ductility. This change of mechanical properties was closely associated with a deformation behavior. Furthermore, the deformation behavior was affected by the critical resolved shear stress of Cu-rich and Cu-depleted regions and the uneven stress distribution caused by phase separation. In addition, dislocation slipping and grain boundary sliding were the main mechanisms of plastic deformation in the Co–Cr–Cu–Fe–Ni HEA.